2020
DOI: 10.1111/nyas.14325
|View full text |Cite
|
Sign up to set email alerts
|

Community context for mechanisms of disease dilution: insights from linking epidemiology and plant–soil feedback theory

Abstract: In many natural systems, diverse host communities can reduce disease risk, though less is known about the mechanisms driving this “dilution effect.” We relate feedback theory, which focuses on pathogen‐mediated coexistence, to mechanisms of dilution derived from epidemiological models, with the central goal of gaining insights into host–pathogen interactions in a community context. We first compare the origin, structure, and application of epidemiological and feedback models. We then explore the mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 152 publications
1
24
0
Order By: Relevance
“…These results are consistent with studies in natural ecosystems showing that negative PSF may potentially contribute to overyielding as host‐specific pathogens were likely to be diluted or suppressed by other species (Kulmatiski et al., 2012; Wang et al., 2019). The suppression of pathogens in plant mixtures may be ascribed to pathogen dilution or suppression by other microbes (Collins et al., 2020), as more microbial dissimilarities were found in heterospecific soils (Figure 5). Consistent with pathogen dilution/suppression, we observed that negative PSF in both M&F and W&F systems was reduced by inclusion of a third common species during soil training (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with studies in natural ecosystems showing that negative PSF may potentially contribute to overyielding as host‐specific pathogens were likely to be diluted or suppressed by other species (Kulmatiski et al., 2012; Wang et al., 2019). The suppression of pathogens in plant mixtures may be ascribed to pathogen dilution or suppression by other microbes (Collins et al., 2020), as more microbial dissimilarities were found in heterospecific soils (Figure 5). Consistent with pathogen dilution/suppression, we observed that negative PSF in both M&F and W&F systems was reduced by inclusion of a third common species during soil training (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…If plant communities are regulated by host‐specific pathogens, strong negative specific PSFs should prevail, disease risk should increase with conspecific density, and heterospecific neighbours should reduce specialist pathogen transmission – a process known as pathogen dilution (Keesing et al ., 2006; Collins et al ., 2020). In contrast, the potential of generalist pathogens to induce specific PSFs will depend strongly on plant community composition (Ampt et al ., 2022).…”
Section: Plant–pathogen Interactions As Drivers Of Psfmentioning
confidence: 99%
“…However, by representing the net consequence of disease dynamics on host fitness, feedback theory does predict that when negative feedback predominates, increases in host diversity will result in reduced impact of pathogens on host fitness. Given evidence that root pathogens drive negative microbiome feedback in plant communities (Crawford et al, 2019 ), some have argued that impacts of root pathogens will generally be diluted by increasing plant diversity (Collins et al, 2020 ). Moreover, a general argument on the importance of pathogens in structuring plant communities can be constructed by combining inference from the few tests of classic host–pathogen models parameterised to particular systems (Mordecai, 2013b , a ) with the much broader data available on patterns of plant–soil microbiome feedback (Bever et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%